2000
DOI: 10.1038/81380
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of Neisseria meningitidis pathogenesis

Abstract: The pathogenic bacterium Neisseria meningitidis is an important cause of septicemia and meningitis, especially in childhood. The establishment and maintenance of bacteremic infection is a pre-requisite for all the pathological sequelae of meningococcal infection. To further understand the genetic basis of this essential step in pathogenesis, we analyzed a library of 2,850 insertional mutants of N. meningitidis for their capacity to cause systemic infection in an infant rat model. The library was constructed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
168
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(172 citation statements)
references
References 19 publications
4
168
0
Order By: Relevance
“…This is in agreement with the finding in Ralstonia solanacearum that a knockout of ampD, involved in peptidoglycan synthesis, results in decreased plant infection (271). STM showed that Neisseria meningitidis AmpD is necessary during rat infection (267).…”
Section: Genes Involved In Cell Envelope Structure and Modificationsupporting
confidence: 92%
“…This is in agreement with the finding in Ralstonia solanacearum that a knockout of ampD, involved in peptidoglycan synthesis, results in decreased plant infection (271). STM showed that Neisseria meningitidis AmpD is necessary during rat infection (267).…”
Section: Genes Involved In Cell Envelope Structure and Modificationsupporting
confidence: 92%
“…meningitidis has several mechanisms to avoid lysis by the complement system, including sialylation of its LPS and expression of a polysaccharide capsule (21). Strains which express truncated LPS isoforms or lack a capsule are highly susceptible to complement-mediated lysis, and are markedly attenuated in animal models of bacteraemia (22)(23)(24)(25). The serogroup classification of N. meningitidis is based on the chemical composition of its polysaccharide capsule.…”
mentioning
confidence: 99%
“…58,59). STM has been applied to more that 30 pathogens, including MenB, where 65 novel genes required for infection that causes septicemia in infant rats were identified (60), and Helicobacter pylori, where 47 genes essential for colonization of the gerbil stomach were identified (61). Also of interest have been studies using TraSH to identify the mechanisms by which M. tuberculosis persists in the host (62) and those using GAMBIT to determine the complete set of genes required by H. influenzae for growth and viability in vitro (63).…”
Section: Functional Genomics: Essential Genes As Vaccine Candidatesmentioning
confidence: 99%